Influence of uncertainty level on dynamics of capital structure of industrial entities in Ukraine - Nykytiuk, T.O. (Економічний вісник Донбасу, 2010)
In the article pressing theoretical and practical issues with regards to ways of industrial entities adaptation to the new conditions of business in the conditions of market instability with the purpose of capital increase are considered Key words: uncertainty, market instability, capital assets of enterprise, investment, public-private partnership, production potential.